Prevalence, deaths and disability-adjusted life years due to Alzheimer’s disease and other dementias in Middle East and North Africa, 1990–2021 - Fatemeh Amiri; Saeid Safiri; Ali Shamekh; Ali Ebrahimi; Mark J. M. Sullman; Ali-Asghar Kolahi (Scientific Reports, 2025)
Abstract Alzheimer’s disease (AD) ranks among the leading causes of morbidity and mortality worldwide. The objective was to evaluate the burden of AD and other dementias among the countries of the Middle East and North Africa (MENA) region by age and sex from 1990 to 2021. The data were sourced from the Global Burden of Disease (GBD) study 2021. The estimates are presented as counts and age-standardised rates per 100,000 accompanied by 95% uncertainty intervals (UIs). In 2021, AD and other dementias recorded an age-standardised prevalence of 772.7 per 100,000 in the MENA region (95% UI 671.2–877.6 per 100,000). This rate decreased by 4.9% in comparison to 1990, marking a statistically significant change. AD and other dementias also accounted for approximately 73.79 thousand deaths in the region in 2021, with the age-standardised rate decreasing by 8.6% compared to 1990. Moreover, the disability-adjusted life years (DALY) rate was 476.3 per 100,000 population (95% UI 225.6–1004.2), representing a 7.7% decrease from 1990 to 2021. Lebanon registered the highest point prevalence per 100,000 at 828.25, while the United Arab Emirates recorded the lowest at 652.43. The age-standardised point prevalence decreased from 1990 to 2021 in 13 of the MENA countries, while no significant changes were observed in eight of countries. Additionally, in 2021, women experienced higher prevalence rates, DALYs, compared to men. In the MENA region, age-standardised dementia prevalence rose with age in both sexes. The burden of dementia in MENA has decreased from 1990 to 2021, but it remains higher than global estimates. Furthermore, the findings indicate that dementia imposes a greater burden on the female population compared to males. To achieve a more accurate estimation of the burden of Alzheimer’s disease and other dementias, more systematic studies in low- to middle-income countries within the MENA region are required.